Ocular surface ectoderm instigated by WNT inhibition and BMP4 - Kobayashi, Yuki (Stem Cell Res, 2020)
We sought to elucidate how and when the ocular surface ectoderm commits to its differentiation into the corneal epithelium in eye development from human induced pluripotent stem cells (hiPSCs) under the influence of WNT signaling and the actions of BMP4. These signals are key drivers ocular surface ectodermal cell fate determination. It was discovered that secreted frizzled related protein-2 (SFRP2) and Dickkopf1 (DKK1), which are expressed in neural ectoderm, are both influential in the differentiation of hiPSCs, where they act as canonical WNT antagonists. BMP4, moreover, was found to simultaneously initiate non-neural ectodermal differentiation into a corneal epithelial lineage. Combined treatment of hiPSCs with exogenous BMP4 aligned to WNT inhibition for the initial four days of differentiation increased the ocular surface ectodermal cell population and induced a corneal epithelial phenotype. Specification of a surface ectodermal lineage and its fate is thus determined by a fine balance of BMP4 exposure and WNT inhibition in the very earliest stages of human eye development.